Sex Specific Alterations In Autonomic Function In Patients With Irritable Bowel Syndrome. (Journal of Dhaka National Medical College & Hospital, 2013)
Background: Autonomic nerve function impairment is related to development of Irritable Bowel Syndrome (IBS). Heart rate variability (HRV) is a useful tool to measure autonomic nerve function activity and also sympatho-vagal balance.Objective: To assess autonomic nerve function activity by heart rate variability analysis in male and female patients with Irritable Bowel Syndrome.Methods: This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from 1st July 2010 to 30th June 2011.  Ninety patients aged 20-50 years of both sexes with Irritable bowel syndrome were included in the study group. They were collected from the OPD of Gastroenterology in BSMMU. For comparison age and sex matched 30 apparently healthy subjects were also studied as control. The power spectral HRV parameters were recorded by a digital Polyrite. For statistical analysis independent sample t-test was performed as applicable.Results: Mean resting pulse rate, mean HR, SBP, DBP, LF, LF norm and LF/HF were significantly higher and total power, HF, HF norm were significantly lower in female IBS group than male IBS group when compared to those of control.Conclusion: This study concludes markedly lower parasympathetic with concomitant higher sympathetic activity and shifting of sympathovagal balance towards sympathetic predominance in female than that of male IBS patients.J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 19-23